Effects of short-term fatigue on biomechanical and physiological aspects of double poling in high-level cross-country skiers - Zoppirolli, C.; Pellegrini, B.; Bortolan, L.; Schena, F. (Human Movement Science, 2016)
The study aim was to evaluate biomechanical and physiological alterations in double poling technique (DP) after a short-term fatiguing exercise. Eight high-level skiers performed a sub-maximal DP trial (20 km h-1, 1°) before (PRE) and after (POST) a DP test to exhaustion while roller skiing on a treadmill. An integrated analysis of DP technique during PRE and POST included measurement of pole, joint, and centre of mass (COM) kinematics, poling forces, cycle timing, and metabolic parameters. Muscle fatigue in three upper-body muscles was assessed by calculating the Dimitrov` fatigue index (FInms5) of specific electromyographic segments. FInms5 tended to increase in the latissimus dorsi and teres major muscles (P = 0.023 and P = 0.030, respectively) across consecutive DP cycles, as did blood lactate concentration (P = 0.001) and rating of perceived exertion (P = 0.005). The changes indicated a state of fatigue during POST and coincided with the reduction in poling force exertion capacity (P = 0.020). Pole, joint and COM kinematics did not differ between PRE and POST (P > 0.050), whereas recovery phase and cycle times were shorter at POST (P < 0.001 and P = 0.001, respectively). Short-term fatigue led to a reduction in poling force exertion capacity and cycle time in high-level skiers, without altering body and pole kinematics.